Tuntutan ganti kerugian korban perkosaan melalui penggabungan perkara - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstract The Penal Procedure Code regulates the means for case amalgamation incorporating restitution, enabling rape victim demands financial restitution. The objectives of the research are to investigate factors hampering the rape victim's right to take legal action for financial restitution through case amalgamation, and to assess legal attempts that could be undertaken to overcome issues in the Penal Procedure Code regarding regulation on the case amalgamation. Research was undertaken through literature review and field study Using qualitative analysis, it is found that factors limiting the victim's right to acquire financial restitution are the victims 'limited knowledge on their right, victims 'physical and mental fatigue during the course of criminal case process, and limited claim on material loss. Attempts to bridge the regulatory gap in the Penal Procedure Code regarding regulation on case amalgamation are: enabling the police to convey the knowledge of the issue to the victim